Cohesive design of personalized web applications - Schwabe, Daniel; Mattos Guimarães, Robson; Rossi, Gustavo Héctor (2012)
Good software engineering practices, such as separating concerns and identifying patterns, simplify the critical design decisions in building personalized Web applications. The authors use the object-oriented hypermedia design method (OOHDM) for constructing customized Web applications. Incorporating well-known object-oriented design structures and techniques, OOHDM produces flexible Web application models. Designers can add personalized behavior to these models with minimal code manipulation, and reasoning over design objects yields better insight into the personalization process. Although this article casts the discussion in terms of the OOHDM primitives, the ideas presented can be easily applied to other design approaches, such as WebML
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
IEEE Internet Computing, 6(2), pp. 34-43
Keywords: APLICACIONES WEB